Effect of limited-creep feeding on performance of spring-born calves: results of 1988 field trials - Simms, D.D.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two field trials were conducted to evaluate limited-creep feeding of spring- born calves using pelleted creep rations with either 0.5, 5, or 10% salt. Average daily gain was increased (P<.05) over controls in trial 2 and when both trials were combined. However, intakes were higher than desired and feed conversion much poorer than expected.
Keywords: Beef; Limited-creep feeding; Spring calves; Performance